Lean Six Sigma untuk Minimasi Pemborosan pada Proses Penyamakan Kulit Domba - Rahayu Khasanah; Grace S Kojoba; Argaditia Mawadati (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
PT. Adi Satria Abadi is a company engaged in the leather industry. The research was carried out at the first location of the factory located in Bantul district, Yogyakarta. In the leather sheet production process, there is still some waste: Waste defect, in August 2021 there were 6,559.55 Sf of rework products from 161.9965 Sf of leather with a percentage of 4% rework products. As well as the waste of waiting time during manual drying, repetition of activities when transferring leather from hanging to milling, and the distance between dyeing stations to setters and hanging to milling.Based on the results of the analysis, the causes of waste include: Waiting time (cloudy weather), transportation waste (factory layout is not good), motion waste (the closest access to hanging is only through the setter section), rework toggle (skin pull is not strong because the operator is tired) and rework buff (operator misread the information and skin maturation in the tanning process is not good).The recommendations for improvement are adding a blower unit in the manual drying (hanging) section, rearranging the factory layout to minimize transportation and motion waste, adding rest hours and adding 2 fan units in the toggle room. Improving accuracy, and coordination between operators and foremen in the shaving section as well as improving the implementation of SOP in the tanning process.